HUBUNGAN ANTARA AGRESI RELASIONAL DAN SELF-ESTEEM MAHASISWI UNIVERSITAS X - Harianto, Erika; Matahari, David; Ariela, Jessica (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2017)
Abstract — The present study examines the relationship between relational aggression and self-esteem. Participants of this study were 281 active student of University X aged 18-25 years. Data collection was done by employing online questionnaires. The questionnaires included three measuring instruments that have been adapted to the Indonesian language, which were Rosenberg Self-Esteem Scale, Self-Report of Aggression and Social Behavior Measure, and the Marlowe-Crowne Social desirability Scale Form C. The results showed that there is no significant correlation between relational aggression and self-esteem. Other findings related to the research variables are also discussed in the present study. Abstrak — Penelitian ini bertujuan untuk menguji hubungan antara agresi relasional dan self-esteem mahasiswi. Partisipan dari penelitian ini terdiri dari 281 mahasiswi aktif Universitas X yang berusia 18-25 tahun. Peneliti menggunakan kuesioner secara online untuk mengumpulkan data. Kuesioner mencakup tiga alat ukur yang sudah diadaptasi, yaitu Rosenberg Self-Esteem Scale, Self-Report of Aggression and Social Behavior Measure, dan Marlowe-Crowne Social Desirability Scale Form C. Hasil penelitian menunjukkan bahwa tidak adanya korelasi yang signifikan antara agresi relasional dan self-esteem. Penemuan lainnya terkait dengan variabel penelitian juga didiskusikan dalam penelitian ini.